Music Therapy for Preterm Infants and Their Parents: A Cluster-Randomized Controlled Trial Protocol. (29th February 2020) - Yakobson, Dana; Arnon, Shmuel; Gold, Christian; Elefant, Cochavit; Litmanovitz, Ita; Beck, Bolette Daniels
Abstract: Music therapy (MT) interventions and skin-to-skin care (SSC) both aim to address the varied needs of preterm infants, including sensory regulation and stress reduction, inclusion of parents in their infant's care, support of parents' emotional state, and enhancing the parent–infant attachment process. Few studies have investigated the combination of both modalities through randomized controlled trials. Evidence of longer-term effects is missing. This article presents a study protocol that will investigate the effects of combined family-centered MT intervention and SSC on preterm-infants' autonomic nervous system (ANS) stability, parental anxiety levels, and parent–infant attachment quality. 12 clusters with a total of 72 preterm infants, with their parents, will be randomized to one of two conditions: MT combined with SSC or SSC alone. Each parent–infant dyad will participate in 3 sessions (2 in the hospital and a 3-month follow-up). The primary outcome of preterm infants' ANS stability will be measured by the high frequency power of their heart rate variability. Secondary outcomes will be physiological measures and behavioral states in infants and anxiety and attachment levels of parents. This trial will provide important, evidence-based knowledge on the use of the "First Sounds: Rhythm, Breath, and Lullaby" model of MT in neonatal care, through an intervention that is in line with the Newborn Individualized Developmental Care and Assessment Program model for supportive developmental care of preterm infants and their parents. Ethical approval (no. 0283-15) was granted from the local Institutional Review Board in April 2017. This trial is registered in ClinicalTrials.gov, NCT03023267.